The Entrepreneur magazine small business advisor (Entrepreneur magazine small business series, 1999)
Written to meet all the information needs of entrepreneurs, small business owners, and those thinking about going into business for themselves, this practical, user-friendly guide tells you everything you need to know about setting goals and objectives, assessing risk, finding the right location, financing, marketing, pricing, taxation, insurance, record keeping, personnel management, purchasing, inventory, time and stress management, legal matters, advertising, sales, obtaining expansion capital, and many other topics of vital importance to smart, enterprising businesspeople like you.